2012
DOI: 10.1111/echo.12015
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and Diastolic Ventricular Function Assessed by Tissue Doppler Imaging in Children with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is associated with elevated cardiovascular risk even during childhood. Tissue Doppler is a sensitive technique for the assessment of ventricular dysfunction with relatively little data available in children with CKD. We report a prospective cross-sectional echocardiographic study at a tertiary center. Forty-nine patients with median (range) age 11.2 years (6.9-17.9), weight 39.6 kg (23.6-99.7) and height 146 cm (122-185). Thirty-one patients were male. Median duration of follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
4
20
2
Order By: Relevance
“…7,8,18,19 In addition, Mitsnefes et al 6 determined low E/A ratios in predialysis pediatric patients as well. Whereas, in another studies in CKD patients, E/A ratios were similar to that in healthy children, in contrast to Mitsnefes et al 9, 10 We also did not find any significant difference in E/A ratios between the patient and control groups. However, cPWD is influenced by several factors, such as preload and left atrial pressure, and this may explain the controversial results related to the E/A ratios in patients with CKD.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…7,8,18,19 In addition, Mitsnefes et al 6 determined low E/A ratios in predialysis pediatric patients as well. Whereas, in another studies in CKD patients, E/A ratios were similar to that in healthy children, in contrast to Mitsnefes et al 9, 10 We also did not find any significant difference in E/A ratios between the patient and control groups. However, cPWD is influenced by several factors, such as preload and left atrial pressure, and this may explain the controversial results related to the E/A ratios in patients with CKD.…”
Section: Discussioncontrasting
confidence: 69%
“…In another study, 26 although predialysis and dialysis patients had increased LV mass, LV performance and contractility at rest, it was shown that contractile reserve diminished during exercise in the cohort of dialysis. Simpson et al 10 determined that S 0 values were reduced compared with normal, and negatively correlated with patient age. In their study, they used age specific z-scores of measurements because raw TDI values were influenced by patient age, whereas, Lindblad et al 9 observed that S 0 values were not significantly different between reference and predialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations